OPTIMIZATION OF CULTIVATION CONDITIONS OF A NEWLY ISOLATED STRAIN CHLORELLA SP. LH2 FOR COOKING COCOON WASTEWATER TREATMENT - Le, Thi Anh Tu (Trường Đại học Đà Lạt, 2024)
Cooking cocoon wastewater contains large quantities of biodegradable nutrients such as nitrogen, phosphorous, and other compounds that microalgae can consume for their growth. In this study, locally isolated Chlorella sp. LH2 was investigated as a means to remove contaminants in wastewater treatment. This alga can grow under a wide range of cultivation conditions. The results showed that Chlorella sp. LH2 grew well in cocoon wastewater and removed nutrients. The optimal cultivation conditions were determined for a variety of initial dry cell densities, temperatures, pH, and light-dark cycles. The maximum growth rate of Chlorella sp. LH2 was achieved at 25 °C, a pH of 8, a light-dark cycle of 16:08, and an initial dry cell density of 1.5 mg/l. Chlorella sp. LH2 exhibited nutrient removal efficiencies of 89.84%, 90.01%, and 93.44% for total nitrogen, NH4+-N, and total phosphorous, respectively. The high BOD5 and COD removal efficiencies of 91.78% and 87.34%, respectively, indicate that Chlorella sp. LH2 can be considered an ideal microalga to treat cooking cocoon wastewater and is worthy of further applications.